Yaws: The forgotten tropical skin disease - Nadiah Md Alwi (Academy of Family Physicians of Malaysia, 2021)
Yaws is a rare skin disease endemic to tropical countries caused by Treponema pertenue. It is highly infectious and spreads through physical contact. In Malaysia, it was presumably eradicated during the 1960s, with the last reported case published in 1985. Due to its rarity, the disease often goes unrecognised and misdiagnosed. Here, we report the case of a 5-year-old aboriginal boy diagnosed with secondary yaws who presented with fever and an incidental finding of chronic painless ulcerated nodules and plaques on his lower limbs and gluteal region. His diagnosis was confirmed serologically with a venereal disease research laboratory lab test and he was successfully treated with a single dose of intramuscular benzathine penicillin G. Primary care physicians should not ignore this disease since its early recognition and appropriate treatment is vital to its eradication, especially in high-risk communities.